The Potential of Outing Class Acitivities to Enhance Environmental Awareness for Elementary School Pre-Services Teacher - Siti Patonah; Sentot Budi Rahardjo; Cari Cari; Sajidan Sajidan (International Journal of Pedagogy and Teacher Education, 2018)
Environmental damage in various places requires concrete steps to be resolved. The purpose of this research is to make environmental awareness work for Elementary School Pre-services Teacher through outing class activities. Post-test only group design is used as a method of this research. The instruments used are environmental awareness questionnaire where adapted. There are 71 elementary pre-service teacher  (60 male and 11 female) who fill in questioner. Students devide into 2 groups: experiment group and control group. Data analysis is an independent sample test using SPSS vol. 22. Experiment group, learning is done by outing class while the control group is done in the classroom. Obtained significance of 0.029 < 0.05, indicating that there is a difference between the experimental group and the control group. Outing class has an effect on environmental awareness to elementary school pre service teacher. An in-depth study is required to modify outing class activities in enhancing environmental awareness.